2013
DOI: 10.1002/jmv.23853
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and analytical relevance of NNRTIs minority mutations on viral failure in HIV‐1 infected patients

Abstract: The objective of this study was to assess the analytical and clinical relevance of minority variants using a new pyrosequencing (PSQ) assay and to detect minor variants with frequencies below the current 20% clinical setting limit. A PSQ approach for detecting and quantifying mutations was developed for the analysis of 14 codons of the human immunodeficiency virus (HIV) reverse transcriptase (RT) gene below the limit of conventional sequencing. Ten patients who experienced virological failure (VF) after a firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Previous studies [27–39] have reported that individuals initiating cART with preexisting HIV low-frequency DRMs have a higher likelihood of VF, particularly among those initiating NNRTIs. It has also been reported that individuals with preexisting low-frequency DRMs at baseline have the same DRMs at the time of VF.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [27–39] have reported that individuals initiating cART with preexisting HIV low-frequency DRMs have a higher likelihood of VF, particularly among those initiating NNRTIs. It has also been reported that individuals with preexisting low-frequency DRMs at baseline have the same DRMs at the time of VF.…”
Section: Introductionmentioning
confidence: 99%
“…Retrieving HIV resistance data from PBMC may be less expensive, but the clinical significance of DRM in proviral DNA remains controversial [ 9 , 15 17 ]. Moreover, consensus genotype from plasma RNA or proviral DNA does not detect DRM as minority variants <20% [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…By comparison with cloning and sequencing, we estimate that at least 20% mutant was necessary in the patient’s specimens to be detected by the PCR-SSOP-Luminex assay. The sensitivity of detection by Sanger sequencing has been reported to be ∼20% [33] , [34] . Sanger sequencing and PCR-SSOP-Luminex had approximately the same detection sensitivity on patient materials.…”
Section: Discussionmentioning
confidence: 99%